APAKAH INDEKS PEMBANGUNAN MANUSIA DAN TINGKAT PENGANGGURAN BERDAMPAK TERHADAP PEREKONOMIAN DI KERESIDENAN BANYUMAS? - Purba, Samuel Fery (Jurnal Inovasi Daerah, 2023)
One of the indicators of economic growth is quality human development, which is measured in three aspects: a decent standard of living, health, and education. Inequality in human development persists in the Banyumas Residency area, impacting the regional economy. The aim of the study is to examine the correlation between mean years of schooling, human development index, and unemployment rate to GRDP per capita (proxy of economic growth) in Banyumas Residency, Central Java. Secondary research data comes from the Statistics Indonesia website. The research method uses panel data regression, consisting of time series data for 2017–2022 and cross-sectional data from 4 areas in Banyumas Residency, namely Banyumas Regency, Purbalingga Regency, Cilacap Regency, and Banjarnegara Regency. The Fixed Effect Model is the chosen estimation model in answering the research hypothesis. The research findings state that the human development index has a significant positive correlation with GRDP per capita. The unemployment rate has a significant negative correlation with GRDP per capita. Meanwhile, the mean years of schooling has an insignificant positive correlation with GRDP per capita. The conclusion of the study is that there is a relationship between the Human Development Index and the unemployment rate on the economy in the Banyumas Residency.